The Difference of Intelligence Quotient (IQ) Score Before and After Temporal Lobe Epilepsy (TLE) Surgery: A Quasi-Experimental Study in Indonesia - Muhamad Thohar Arifin (Journal of Global Pharma Technology, 2019)
Background: Epilepsy is a serious disorder of the brain, affects almost fifty million people in the world. About 40% of the patients finally became refractory to epileptic drugs, especially those with temporal lobe epilepsy (TLE). Surgical therapy has an important role in stopping further damage to brain cells caused by repeated seizures. The elimination of the seizure after surgery will hopefully result in better intelligence score. This study aims to find out the effect of surgical therapy in TLE patients on the Intelligence Quotient (IQ) score. Method: A quasi-experimental study with pre-test and post-test group design was conducted among 15 respondents. The respondents were taken with consecutive sampling method that underwent anterior temporal lobectomy and have passed at least one-year postoperative period, and also had done an intelligence quotient (IQ) test before surgery. IQ before and after surgery were measured with WAIS and WISC-R method. The statistical tests used were paired t-test by SPSS version 20 for Windows. Result: Most of the respondents were males (66.7%), average age 24.3±7.17 years-old, and 7.7±4.70 year’s duration of seizures. The verbal IQ score after surgery was 98.8±9.88 significantly higher (p=0.01) compared with preoperative verbal IQ (92.7±9.60) score. On the other hand, the performance IQ score after surgery was higher (98.2±8.64) compared with preoperative performance IQ (96.0±9.39), however not statistically significant (p=0.5). A total IQ score after surgery tends to be higher (97.8 ±7.69) compared with preoperative total IQ (93.9±9.28) but not statistically significant (p=0.08).  Conclusion: Our study suggests that postoperative verbal IQ improvement was found to be significantly different compared to the preoperative verbal IQ. However, there was no significant difference in the performance and total IQ score after TLE surgeryKeywords: IQ, Epilepsy, Temporal lobe epilepsy, Surgery.